POST-TRAUMATIC STRESS AND COGNITIVE FUNCTIONING AFTER DISASTER: IS SLEEP DISTURBANCE AND IMPAIRMENT RESPONSIBLE?. (11th November 2018) - Stanko, K; Calamia, M; Cherry, K; Elliott, E
Abstract: In the aftermath of a natural disaster, some individuals will exhibit symptoms of post-traumatic stress disorder (PTSD), including chronic sleep disturbance and impaired cognitive function. Older adults may be particularly vulnerable due to typically higher sleep disruption than younger adults. We tested mediational models to further explore the positive relationship between PTSD symptoms and deficits in cognition, including subjective, self-report measures of applied cognition and executive functioning, and objective, behavioral tasks of working memory and attention/vigilance. Participants were mostly middle-aged and older adults who were indirectly and directly exposed to the Great Flood of 2016 flooding in Baton Rouge, LA. These persons completed a variety of cognitive tasks and health-related measures across three days of testing. PTSD symptomology was measured through the PTSD Checklist- Civilian Version, subjective cognition through the PROMIS Applied Cognition and Barkley Deficits in Executive Functioning Scales, and objective cognition through Working Memory Composite (WMC) and Sustained Attention to Response Task (SART) scores. Using subjective cognition as the outcome variable, sleep disturbance and impairment significantly mediated the relationship between PTSD symptoms and self-reported cognitive impairment. For the objective cognition outcomes, WMC and SART, we did not find any significant relationship between PTSD, sleep disturbance, and performance on either measure. These results imply that people's self-reports of cognitive functioning in relation to PTSD are impacted by their quality of sleep. After disaster, interventions to improve sleep alone may benefit traumatized survivors, including older adults, leading to higher self-perceptions of one's cognitive functioning.